We use cookies to personalise content and advertisements and to analyse access to our website. Furthermore, our partners for online advertising receive pseudonymised information about your use of our website. cookie policy and privacy policy.
 
+0  
 
0
54
2
avatar

\(\begin{array}{ccccccccccc}  \\ & & & & & 1   \\ & & & & 2 & & 2   \\ & & & 3 & & 4 & & 3   \\ & & 4 & & 7 & & 7 & & 4  \\ & 5 & & 11 & & 14 & & 11 & & 5  \\ 6 & & 16 & & 25 & & 25 & & 16 & & 6 \end{array} \)

If we form a number triangle as above, what is the sum of all the numbers in the triangle with 20 rows? 

 Nov 2, 2019

Best Answer 

 #1
avatar
+1

This is the closed form of your sequence:


a_n = 1/2 (3 2^n - 4)......and it generates all the terms of your sequence as follows:


Sum = (1, 4, 10, 22, 46, 94, 190, 382, 766, 1534, 3070, 6142, 12286, 24574, 49150, 98302, 196606, 393214, 786430, 1572862) = 3,145,685 - which is the sum of the first 20 rows.

 Nov 2, 2019
 #1
avatar
+1
Best Answer

This is the closed form of your sequence:


a_n = 1/2 (3 2^n - 4)......and it generates all the terms of your sequence as follows:


Sum = (1, 4, 10, 22, 46, 94, 190, 382, 766, 1534, 3070, 6142, 12286, 24574, 49150, 98302, 196606, 393214, 786430, 1572862) = 3,145,685 - which is the sum of the first 20 rows.

Guest Nov 2, 2019
 #2
avatar+23516 
+1

help

\(\begin{array}{lccccccccccc} \text{row }1:& & & & & & 1 \\ \text{row }2:& & & & & 2 & & 2 \\ \text{row }3:& & & & 3 & & 4 & & 3 \\ \text{row }4:& & & 4 & & 7 & & 7 & & 4 \\ \text{row }5:& & 5 & & 11 & & 14 & & 11 & & 5 \\ \text{row }6:& 6 & & 16 & & 25 & & 25 & & 16 & & 6 \end{array} \)

If we form a number triangle as above,

what is the sum of all the numbers in the triangle with 20 rows?

 

\(\text{Let row $=r$} \\ \text{Let the sum of all the numbers in the rth row $=s_r$ } \\ \text{Let the sum of the numbers in the triangle from 1 to rth row $=s_{1\ldots r}$ }\)

 

\(\begin{array}{|rcll|} \hline s_1 &=& 1 \\ s_2 &=& 1 +3\cdot( 1 ) \\ s_3 &=& 1 +3\cdot( 1+2 ) \\ s_4 &=& 1 +3\cdot( 1+2+4 ) \\ s_5 &=& 1 +3\cdot( 1+2+4+8 ) \\ s_6 &=& 1 +3\cdot( 1+2+4+8+16 ) \\ \ldots \\ s_r &=& 1 +3\cdot( 1+2^1+2^2+2^3+2^4+\ldots + 2^{r-2} ) \\ &=& 1+ 3\cdot(2^{r-1}-1) \\ \mathbf{s_r} &=& \mathbf{ 3\cdot 2^{r-1} -2 } \\ \hline \end{array} \)

 

 

\(\begin{array}{|rcll|} \hline s_{1\ldots r} &=& \sum \limits_{i=1}^{r} \left(3\cdot 2^{i-1} -2 \right) \\ &=& 3\sum \limits_{i=1}^{r} \left(2^{i-1}\right) -\sum \limits_{i=1}^{r} 2 \\ &=& 3\sum \limits_{i=0}^{r-1} \left(2^i\right) -2\sum \limits_{i=1}^{r} 1 \\ &=& 3\sum \limits_{i=0}^{r-1} \left(2^i\right) -2r \\ &=& 3\sum \limits_{i=0}^{r} \left(2^i\right) -3\cdot2^r -2r \quad | \quad \sum \limits_{i=0}^{r} \left(2^i\right) = \left( 2^{r+1}-1 \right) \\ &=& 3\cdot \left( 2^{r+1}-1 \right) -3\cdot2^r -2r \\ &=& 3\cdot 2^{r+1}-1 -3 -3\cdot2^r -2r \\ &=& 3\cdot \left(2^{r}\cdot 2 \right) -3\cdot2^r -2r -3 \\ &=& 2^{r}\left( 6-3\right) -2r -3 \\ \mathbf{ s_{1\ldots r} } &=& \mathbf{ 3\cdot 2^{r} -2r -3 } \\ \hline \end{array}\)

 

\(\begin{array}{|rcll|} \hline \mathbf{ s_{1\ldots r} } &=& \mathbf{ 3\cdot 2^{r} -2r -3 } \quad | \quad r = 20 \\\\ s_{1\ldots 20} &=& 3\cdot 2^{20} -2\cdot(20) -3 \\ &=& 3\cdot 2^{20} -2\cdot(20) -3 \\ &=& 3\cdot 2^{20} -43 \\ &=& 3\cdot 1048576 -43 \\ &=& 3\cdot 1048576 -43 \\ &=& 3145728 -43 \\ \mathbf{ s_{1\ldots 20} } &=& \mathbf{ 3145685} \\ \hline \end{array}\)

 


laugh

 Nov 3, 2019

9 Online Users

avatar